A Parametric Study of Functionally Graded Rotating Annular Fin. (2015) - Gaba, Vivek Kumar; Tiwari, Anil Kumar; Bhowmick, Shubhankar
Abstract: Performance analysis of the rectangular annular fins made of functionally graded material subjected to rotation is reported in the present work. The governing differential equation for the fins has been derived to study the temperature distribution of the fins with insulated tip. A parametric study is then carried out by varying grading parameters along with the parameter of dimensionless rotational speed of the shaft in the governing equation to investigate the effect of on fin performance. The results are presented in graphical form. The formulation is validated with benchmark results and good agreement is observed.